Detection of Cryptosporidium spp. (Tyzzer, 1907) (Apicomplexa: Cryptosporidiidae) in dogs in southern Brazil - Ferraz, Alexsander (2025)
Cryptosporidium spp. is a protozoan of the phylum Apicomplexa that affects the gastrointestinal tract of humans and animals. Infection occurs mainly through the fecal-oral route, by ingesting infectious oocysts present in contaminated water or food. The clinical signs of cryptosporidiosis are usually nonspecific and include profuse, watery, yellowish diarrhea with a foul odor. This study aimed to determine the occurrence of Cryptosporidium spp. in dogs in the municipality of Pelotas, in the extreme south of Brazil. A total of 150 canine fecal samples were analyzed, with 75 from domiciled dogs and 75 from stray or semi-domiciled dogs. Oocyst detection was performed using the modified Ziehl-Neelsen staining technique. Of the analyzed samples, 5.3% (8/150) were positive for Cryptosporidium spp. Among stray or semi-domiciled dogs, 8% (6/75) were positive, while in domiciled dogs, the rate was 2.7% (2/75). Due to its zoonotic potential and the close contact between animals and humans, the results suggest that dogs may act as a potential source of human cryptosporidiosis infection